Preparation of Cellulose Pineapple (Ananas comosus) Peel as Adsorbent of Remazol Yellow Dye - Lestari, Intan; Permana, Edwin; Hidayat, Dara Shalsa Billah; Wijaya, Dhian Eka (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
The extraction of cellulose from pineapple (Ananas comosus) peel has been carried out through delignification using alkaline and hydrolysis with acid. The extraction of cellulose was carried out by de-waxing, delignification followed by hydrolysis with H2SO4 acid. The cellulose obtain was identified by FTIR and SEM-EDS. The results showed that the FTIR spectra of pineapple peel cellulose contain hydroxyl and carboxyl functional groups which useful in the adsorption process. The morphology of cellulose has a more homogeneous and porous shape. The cellulose obtained was used for adsorption of Remazol yellow dye by studying adsorption parameters, namely the effect of pH, contact time and solution concentration. The adsorption process was obtained at pH 2, the optimum contact time was 30 minutes and concentration at 100 mg/L with an adsorption capacity is 19.888 mg/g.